2019
DOI: 10.1021/acs.jpcc.9b04432
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Separation of CO2/CH4/Brine with Amorphous Kerogen: A Thermodynamics and Kinetics Study

Abstract: Carbon dioxide (CO 2 )-enhanced oil recovery and sequestration are both processes that are associated with the separation and storage of gas in organic-rich shale formations. The current study investigates the applicability of kerogen, an amorphous and insoluble organic matter abundant in unconventional shale formations, for the separation of the mixture of gases (CO 2 and CH 4 ) in dry and wet (brine) conditions for an effective storage and injection operation. Here, through molecular dynamics, thermodynamics… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
2

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 32 publications
0
21
0
Order By: Relevance
“…In another study, Ho et al 33 showed that methane release in nanoporous kerogen matrices is characterized by a fast release of pressurized free gas (accounting for less than 50% recovery), followed by a slow release of adsorbed gas as the gas pressure decreases. There are still other related molecular‐level simulation studies on enhanced shale gas recovery by carbon dioxide and CO 2 sequestration in kerogen matrices of different maturity and porosity, see, for example 34‐40 …”
Section: Introductionmentioning
confidence: 99%
“…In another study, Ho et al 33 showed that methane release in nanoporous kerogen matrices is characterized by a fast release of pressurized free gas (accounting for less than 50% recovery), followed by a slow release of adsorbed gas as the gas pressure decreases. There are still other related molecular‐level simulation studies on enhanced shale gas recovery by carbon dioxide and CO 2 sequestration in kerogen matrices of different maturity and porosity, see, for example 34‐40 …”
Section: Introductionmentioning
confidence: 99%
“…19,20 Next, to understand gas adsorption in a mixture of uids, including CH 4 and CO 2 , the interactions that take place between CH 4 , CO 2 , and aqueous brine in nano-pores of the organic compound was examined. 21 The present work is the extension of our previous studies into the innitely diluted hydrocarbons in SC-CO 2 and aqueous brine. In particular, we analyzed the interactions between molecules in such mixtures and estimated D of aromatics and aliphatic hydrocarbons in the presence of SC-CO 2 and aqueous brine concentrations.…”
Section: Introductionmentioning
confidence: 80%
“…15 In addition to the development of the molecular models for this purpose, the computational techniques have also become frequent tools for simulating the gas adsorption and desorption processes. [16][17][18] Simulation of adsorption behavior is important since organic rich shales are becoming a repository of green house gases storage which can also improve their productivity in CO 2 enhanced oil recovery (EOR) and sequestration.…”
Section: Introductionmentioning
confidence: 99%
“…The Bakken Formation is one of the largest unconventional shale oil plays in North America and is currently being studied for potential CO 2 -enhanced oil recovery and sequestration; 19 recent studies suggest that an injection of CO 2 into organic−rich shales can increase their production potential. 16,19 Hence, in order to precisely estimate the capacity of organic matter in terms of adsorption for sequestration and/or associated mechanisms for enhanced oil recovery, building a 3D molecular model of the Bakken kerogen has become imperative. Here, we report a new representative molecular model for organic matter from the Bakken (kerogen type II) based on previously experimental chemical compositional data.…”
Section: Introductionmentioning
confidence: 99%